2001
DOI: 10.1007/0-306-47915-x_1
|View full text |Cite
|
Sign up to set email alerts
|

The Spin Structure of the Nucleon

Abstract: We present an overview of recent experimental and theoretical advances in our understanding of the spin structure of protons and neutrons.Comment: 84 pages, 29 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
207
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(220 citation statements)
references
References 296 publications
10
207
0
1
Order By: Relevance
“…We use gauge field configurations with 2 þ 1 flavors of nonperturbatively OðaÞ-improved Wilson fermions and a lattice volume of L 3 × T ¼ 32 3 × 64. The lattice spacing a ¼ 0.074ð2Þ fm is set using a number of singlet quantities [29][30][31][32].…”
Section: Simulation Detailsmentioning
confidence: 99%
“…We use gauge field configurations with 2 þ 1 flavors of nonperturbatively OðaÞ-improved Wilson fermions and a lattice volume of L 3 × T ¼ 32 3 × 64. The lattice spacing a ¼ 0.074ð2Þ fm is set using a number of singlet quantities [29][30][31][32].…”
Section: Simulation Detailsmentioning
confidence: 99%
“…(14). In this case one gets, among the others, the Collins function, ∆ N D C/q ↑ , and a chiral-even TMD fragmentation function of an unpolarized quark into a transversely polarized hadron (denoted consistently as ∆ N D C ↑ /q ).…”
Section: Parton Model Approaches Including Intrinsic Transverse Motionmentioning
confidence: 99%
“…The rich, low-energy aspects of topics iii) and iv), which may be confronted only with nonperturbative approaches, will also remain uncovered. A comprehensive overview on these subjects and on related topics can be found in several review papers, addressing both their theoretical and experimental aspects [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. Here we will focus on the high-energy regime and the treatment in the context of pQCD approaches of transverse SSA's and, marginally, of the transverse polarization of spin 1/2 particles in unpolarized processes.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, it has been observed that the total nucleon momentum and spin are not exhausted by the quark contribution alone, and a large debate has originated on the involved quark-gluon dynamics (for a recent review, see Ref. [2]). …”
Section: Introductionmentioning
confidence: 99%